Characteristics of Crude Pepsin Enzyme from Catfish Stomach (Clarias sp.) - Fatiranes, Erlando; Sidauruk, Santhy Wisuda; Hasan, Bustari (Aquatic Life Sciences, 2025)
Fish stomach is a by-product of the fishing industry that has potential as a natural source of pepsin enzyme, particularly from catfish (Clarias sp.). This study aimed to characterize crude pepsin extracted from catfish stomachs. The extraction was carried out by homogenizing the stomach with 10 mM Tris-HCl buffer (pH 7.5), followed by centrifugation at 10,000 g for 15 min at 4°C. The obtained pepsinogen was activated using 3 N HCl at pH 2 and neutralized to pH 2.75 with 2 N NaHCO₃. Enzyme activity was determined using the hemoglobin assay at 280 nm, and protein concentration was measured by the Bradford method at 595 nm. The crude pepsin showed an activity of 33.50 ± 0.87 U/mL, protein concentration of 0.358 ± 0.005 mg/mL, total activity of 1,608 ± 41.57 U, and specific activity of 93.52 U/mg. The enzyme exhibited optimal activity at 50°C and pH 4, with relative activity toward NaCl, ZnCl₂, and FeCl₃ of 81.08%, 49.10%, and 128.15%, respectively, indicating Fe³⁺ acted as an activator. These results demonstrate that catfish stomachs can serve as a potential halal-compatible pepsin source, supporting enzymology advancement and fish waste valorization.